L’ARRET DU CONSEIL D’ETAT DU 22 MAI 2023 DANS L’AFFAIRE POLICE JUDICIAIRE DES PARQUETS CONTRE LA REPUBLIQUE DEMOCRATIQUE DU CONGO. LECTURE ET COMMENTAIRES - MANDEFU MUELA Mechack & KUBANZILA MUZELA Elvis (Ziglôbitha)
Abstract : Teaching writing presents significant challenges, particularly in the evaluation of students' written work. Despite the considerable time that writing teachers invest in reading and comprehending their students’ compositions, they often struggle to provide fair assessments and appropriate scores, especially during examinations. To address these challenges, the present study explores the effectiveness of a paragraph analytic rubric as a tool for assessing students' writing. This rubric aims to unify evaluation criteria and ensure consistent scoring across all students. Developed by the researcher, the rubric has been implemented by second-year EFL writing teachers at the Department of English, Sétif 2 University, during the first semester writing exams over three consecutive years. In this action research project, teachers participated in a questionnaire and focus group discussion that assessed their satisfaction with the paragraph rubric, revealing positive feedback regarding its utility in grading exams. The findings from this research contribute to the establishment of clear assessment criteria for formal exams that require paragraph writing. By employing this rubric, the study seeks to enhance the reliability and fairness of writing assessments, ultimately improving both teaching practices and student learning outcomes in EFL contexts. Keywords: Analytic rubric, Exam Evaluation, Paragraph writing, Rubric creation, Writing teacher.